2020
DOI: 10.1186/s40337-020-00330-3
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and self-reported body image in German adolescents

Abstract: Background Despite knowledge about eating disorder symptoms in children and adolescents in the general population, relatively little is known about self-reported and sex-specific eating-disorder-related psychopathology, as well as its specific correlates. Methods 880 German school-attending adolescents (15.4 ± 2.2 years) and 30 female patients with AN (16.2 ± 1.6 years) were studied. All participants completed the Eating Disorder Inventory-2 and a Body Image Questionnaire. Results There were more overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Moreover, self-efficacy has a positive impact on self-esteem [51] as one of the core factors of body image [34]. Thus, the current study extends those findings to demonstrate that behind relationships between body image and weight reduction behaviour [8,52], including symptoms for eating disorders [36,53], the health literacy may play a significant role in establishing adolescents' body image and subsequently symptoms for eating disorders. On the other hand, the nature of the HLSAC measurement tool used in this study is based on beliefs in one's own competences (i.e., self-efficacy) [45], and thus the self-perceived indicators may tend to group together [21].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, self-efficacy has a positive impact on self-esteem [51] as one of the core factors of body image [34]. Thus, the current study extends those findings to demonstrate that behind relationships between body image and weight reduction behaviour [8,52], including symptoms for eating disorders [36,53], the health literacy may play a significant role in establishing adolescents' body image and subsequently symptoms for eating disorders. On the other hand, the nature of the HLSAC measurement tool used in this study is based on beliefs in one's own competences (i.e., self-efficacy) [45], and thus the self-perceived indicators may tend to group together [21].…”
Section: Discussionsupporting
confidence: 73%
“…To this end, Álvarez [75] emphasised the same conclusion, which is that body image influences both the physical and general self-concept, and for this reason, males show higher levels of self-concept as self-perceptions of the physical image in females tend to be harsher. Given the importance of this aspect, several authors emphasised the importance of promoting a healthy body image given the link identified among body dissatisfaction, high BMI and a negative physical self-concept, especially attractiveness [25,[80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a critical period for body image development because of the various social, cultural, physical, and psychological changes occurring between the ages of 12 years and 18 years. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…Adolescents’ perceptions of their body image rest on some psychosocial concepts: the social idea of the ideal body and everyday comparison among people. 13 14 15 16 17 18 19 …”
Section: Introductionmentioning
confidence: 99%